Elementary logic for philosophy of science and economic methodology - Max Albert (Philipps-University Marburg, School of Business and Economics, 2015)
This paper covers those parts of elementary logic that are needed in an introductory course on philosophy of science and the methodology of economics. With this aim in mind, much of the technical material from standard logic courses can be dropped. Specifically, the exposition emphasizes the semantic side, with only a few remarks on syntactical aspects. On the other hand, some philosophical and methodological remarks are in order to prepare the ground for methodological discussions. Where appropriate, exercises (including review questions and discussion questions) are provided. Solutions to selected exercises are given at the end of the paper.
Keywords: 330